2012
DOI: 10.1021/jm300521m
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-Based Virtual Screening and Biological Evaluation of Small Molecule Inhibitors for Protein Arginine Methylation

Abstract: Protein arginine methyltransferases (PRMTs) are proved to play vital roles in chromatin remodeling, RNA metabolism and signal transduction. Aberrant regulation of PRMT activity is associated with various pathological states such as cancer and cardiovascular disorders. Development and application of small molecule PRMT inhibitors will provide new avenues for therapeutic discovery. We combined pharmacophore-based virtual screening methods with radioactive methylation assays, six hits were identified as inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…Moreover, rattus norvegicus PRMT3 (rPRMT3; PDB code 1F3L) and hPRMT3 (PDB code 3SMQ) structures are established. Since sequence alignments show that mPRMT1 and hPRMT1 are exactly the same within the binding pocket, we built a homology model of hPRMT1 (Zhang and Cheng, 2003;Yan et al, 2014) to process the virtual screening (see Fig. 4B).…”
Section: Homology Modeling and Structure-based Virtual Screeningmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, rattus norvegicus PRMT3 (rPRMT3; PDB code 1F3L) and hPRMT3 (PDB code 3SMQ) structures are established. Since sequence alignments show that mPRMT1 and hPRMT1 are exactly the same within the binding pocket, we built a homology model of hPRMT1 (Zhang and Cheng, 2003;Yan et al, 2014) to process the virtual screening (see Fig. 4B).…”
Section: Homology Modeling and Structure-based Virtual Screeningmentioning
confidence: 99%
“…Similar to the discovery of other novel small-molecule inhibitors (Knutson et al, 2012;Lobera et al, 2013), a virtual screening against an in-house database (15,039 compounds) was first performed (see Materials and Methods). The first few hundred hits were clustered and visually inspected in consideration of the binding mode of known inhibitors of PRMT1 Bissinger et al, 2011;Cheng et al, 2011;Wang et al, 2012a).…”
Section: Development Of Selective Bioactive Prmt1 Inhibitormentioning
confidence: 99%
See 2 more Smart Citations
“…18 A study by Wang et al demonstrated that PRMT1 inhibitors could significantly suppress the growth of castrate-resistant prostate cancer cells. 19 Due to the potential applications of PRMT1 inhibitors in cancer therapy, discovery of PRMT1 inhibitors has recently attracted much attention. To date, a number of PRMT1 inhibitors have been reported.…”
mentioning
confidence: 99%